Development of Teaching Materials on Surface Area of Polyhedron Using Traditional Market Snacks Context and MathCityMap - Kuling, Oriel; Lintang, Agatha; Nugraha, Adhi Surya (JMPM: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to develop mathematics teaching materials on polyhedron surface area using traditional: Jadah, Wajik, Lapet, and Barongko. The cakes were selected for their similarity to geometric shapes as an ethnomathematical link to local culture. This teaching material uses MathCityMap with four activities to find the surface area based on traditional cakes used in different locations. The research employed a Research and Development (R&D) design with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Before limited implementation, the materials were validated by mathematics teachers and PPG Mathematics Education students on content, appearance, and language. The validation results showed that the teaching materials were 96.5% feasible and practical to use. Furthermore, implementation was carried out on a limited basis with 20 Mathematics Education students. It went well and all participants understood every problem presented. Finally, evaluation was used to improve teaching materials based on suggestions from validators.